Sex in the cold: taxonomic reorganization of psychrotolerant yeasts in the order Leucosporidiales. Issue 4 (22nd April 2015) - de García, Virginia; Coelho, Marco A.; Maia, Teresa M.; Rosa, Luiz H.; Vaz, Aline Martins; Rosa, Carlos A.; Sampaio, José Paulo; Gonçalves, Paula; van Broock, María; Libkind, Diego
Abstract : Species of Leucosporidiales are a group of psychrotolerant yeasts with biotechnological potential. In the present work, we studied the phenotypic, genetic and sexual characteristics of three species of this genus ( Leucosporidium scottii, Leucosporidiella creatinivora and Le. yakutica ) to clarify the evolutionary relationship among these closely related taxa. From the results obtained, it becomes clear that these yeasts can interbreed. Although genetic delimitation is possible for the three species, the extent of nucleotide substitutions and phenotypic differences observed between them are lower than that expected for species that have ended the speciation process. Our taxonomic conclusion is to maintain the three taxa until further genomic data are gathered. However, the concept of L. scottii species complex is proposed for this group of species. Finally, we transfer all Leucosporidiella and Mastigobasidium species to Leucosporidium (Leucosporidiales), and, in order to end the polyphyly condition of these taxa, we propose the new genus Pseudoleucosporidium gen. nov. and the new combination Peudoleucosporidium fasciculatum comb. nov. Abstract : Studies on different characteristics (from genetic to sexual behavior) of cold-adapted yeasts species, in order to clarify the evolutionary relationship. Abstract :